FUNGSI AKSARA LAMPUNG DIGITAL UNTUK MEDIA PEMBELAJARAN DALAM KURIKULUM MERDEKA - Alya Agustina; Tri Mukti Aprilia (STKIP Pesisir Selatan, 2025)
This study aims to explore the function and implementation of Digital Lampung Script as a learning medium in the Merdeka Curriculum, which emphasizes flexible, contextual, and competency-oriented learning. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results of the study show that the use of digital media such as Android-based applications and augmented reality (AR) effectively increases students' interest, motivation, and learning outcomes in learning Lampung script. Digital Lampung Script is not only a means of preserving local culture, but also supports the objectives of the Merdeka Curriculum in encouraging creativity, independence, and technology-based learning. In addition, this digital media is able to overcome the limitations of teaching staff and expand access to learning to remote areas. The study also revealed that the development of Digital Lampung Script needs to consider aspects of ease of use, interactivity, and user engagement in order to be used effectively in the learning process. Thus, Digital Lampung Script plays an important role as a bridge between tradition and advances in educational technology, as well as a strategy for preserving Lampung's cultural heritage in the digital age in an adaptive and sustainable manner.